How to Counsel Jewish Clients with Substance Use Disorder: A Motivational Interviewing Approach - Daniel, Adam (Counseling and values, 2024)
Motivational Interviewing, a heavily utilized approach to substance use counseling, has characteristics that make it a culturally sustaining approach to supporting Jewish clients with substance use disorders. The authors address challenges and opportunities in counseling Jewish clients, including identity development and difficulties in addressing mental health and substance use concerns. A case example is provided.